2015
DOI: 10.1089/ten.tea.2014.0173
|View full text |Cite
|
Sign up to set email alerts
|

Cauda Equina-Derived Extracellular Matrix for Fabrication of Nanostructured Hybrid Scaffolds Applied to Neural Tissue Engineering

Abstract: Extracellular matrix (ECM) components have become important candidate materials for use as neural scaffolds for neural tissue engineering. In the current study, we prepared cauda equina-derived ECM materials for the production of scaffolds. Natural porcine cauda equina was decellularized using Triton X-100 and sodium deoxycholate, shattered physically, and made into a suspension by differential centrifugation. The decellularization procedure resulted in the removal of >94% of the nuclear material and preserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…It has been reported that laminins generally tend to polymerize into sheet like structures [ 64 ], which is consistent with our results. Furthermore, similar shifts were also seen after incorporation of laminin onto a poly(l-lactide-co- glycolide) scaffold, indicating successful conjugation of laminin with the nanoribbons [ 65 ]. After conjugation with artemin ( Figure 5 c), further shifts were observed.…”
Section: Resultsmentioning
confidence: 90%
“…It has been reported that laminins generally tend to polymerize into sheet like structures [ 64 ], which is consistent with our results. Furthermore, similar shifts were also seen after incorporation of laminin onto a poly(l-lactide-co- glycolide) scaffold, indicating successful conjugation of laminin with the nanoribbons [ 65 ]. After conjugation with artemin ( Figure 5 c), further shifts were observed.…”
Section: Resultsmentioning
confidence: 90%
“…Before seeding, the scaffolds were sterilized by Co 60 irradiation for 12 h, washed three times with PBS, and immersed in culture medium overnight. DRGs were harvested from rat pups at postnatal day 1 as described previously . The nerve roots were removed, and the DRGs were seeded at the center of the prepared scaffolds in 6‐well plates (Figure S7, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The incorporation of dECM could further amplify this effect through the supplementation of neuro‐inductive biochemical cues. Indeed, the electrospinning of PLGA incorporating porcine cauda equina dECM was shown to support Schwann cell proliferation and axon extension of dorsal root ganglion cells . Similarly, seeding bone marrow–derived mesenchymal stem cells on electrospun genipin‐crosslinked gelatin incorporating rat brain dECM enhanced their expression of the glial fibrillary acidic protein (GFAP), a neural‐specific cell marker …”
Section: Applications Of Processed Decm‐based Materialsmentioning
confidence: 99%
“…As with other processing technologies, synthetic polymers are usually more affordable and more convenient to work with, allowing better control and reproducibility, whereas natural materials offer biocompatibility and biomimicry that are crucial for cellular growth and function . A growing number of studies report the utilization of dECM as the base material for the production of electrospun scaffolds for artificial tissue engineering . To allow a stable dECM electrospinning process, the dECM solution should be made spinnable, i.e., to possess certain viscoelastic properties and to denature the protein tertiary chain conformations .…”
Section: Decm Processing Approachesmentioning
confidence: 99%